An Assessment of The Portuguese Local Governments’ Performance Feedback on The Late Payments Directive - Paula GOMES DOS SANTOS; Fábio ALBUQUERQUE (Communications of International Proceedings, 2023)
Concerns with the government’s indebtedness led the European Commission to issue the Late Payments Directive (LPD) to discourage the culture of late payments that put at risk their financial sustainability. Despite intending to hold the Member States accountable for the public entities’ payment behaviour, the LPD did not settle the methodology underlying the performance feedback. Therefore, this exploratory study aims to assess whether there is evidence of possible gaming strategies by local governments using different categories of liabilities to convey a better image of the Portuguese performance regarding the payment period. Data from the 308 Portuguese local governments were gathered for the period between 2014 and 2019 (the last year available). Using descriptive and Pearson correlation analyses, the findings seem to indicate different patterns of indebtedness over time between the Portuguese local governments with lower and higher PP under the LPD. This paper may contribute to the literature on the gaming behaviours of public organizations by providing insights into the Portuguese local governments' performance feedback on the LPD.
Keywords: Debt; financial sustainability; gaming; Late payments directive; Local governments.